ANALISIS PELAKSANAAN KURIKULUM 2013 KELAS VI DI SDK FRATER XAVERIUS 2 PALEMBANG - Ria Triayomi; Avelina Meita Larassandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2020)
The aims of this study are to describe the analysis result from the implementation of 2013 Curriculum in VI class at SDK Frater Xaverius 2 Palembang, also to describe the constraints and solutions that have been made by the teachers. Analysis of the implementation of the 2013 Curriculum was carried out by comparing the Lesson Plans (RPP) with the Teaching Journal. Researcher assess that material compatibility between planning and implementation was needed. This research is descriptive qualitative research. The subjects in this study are four parallel teachers of class VI and using purposive sampling in determined the subject to analyzed the documentation. Data collection techniques were through interviews with research subjects and document analysis of one teacher from class VI. Data analysis were done by collecting data, reducing data, presenting data, and drawing conclusions. Based on research that has been done, it can be concluded that there are 38.66% similarities and 61.33% differences in class VI material between planning and implementation of the first semester. This is complemented by the results of interviews stating that there is an Iris Curriculum to adjust to the lesson grid provided by the Government. Obstacles faced by teachers are including too much material content, limited time, in-depth material, and the application of character values. The solutions that have been made were providing additional material, utilizing facilities and infrastructure, class outing, also using creative and fun models and methods.